International experience of ensuring cybersecurity in the country and possibility of its application in Ukraine - Pchelina, Oksana Vasilievna; Skulysh, Yevhenii Deoniziyovych; Buglak, Iurii; Myroniuk, Roman Victorovich (DIXI, 2021)
The purpose of this article is to reveal the essence and characteristic features of cybersecurity as one of the most important components of stable functioning of the modern society. Examples of successful experience of developed foreign countries on cybersecurity are considered, and possible ways of its use in Ukraine are offered. In particular, the public’s attention is focused on extremely important issues such as national defense in cyberspace, protection of private legitimate interests of individuals in the network and effective information policy by the state towards citizens. It is noted that the cybersphere has long been one of the most important components of the world society and the world economy. This statement is primarily based on the fact that today more and more banking, trade and other settlement or logistics operations, both within one country and in international relations, are carried out using modern computer, telecommunications and other innovative technologies and devices. It is stated that the sphere of public life, which is outlined in this article, is in dire need of its clear and unambiguous legal regulation. This is especially true in developing countries, including Ukraine. After all, their state system and legal framework are not yet stable and stable. The authors’ definitions of “cybersecurity”, “cyber-subjectivity” and “network sovereignty” are offered. In addition, the relationship between the level of development of the cybersphere in a particular country and the level of its economic development and general financial well-being was studied. It is determined that it is extremely important for Ukraine to adopt the successful experience of some developed foreign countries in the field of protection and processing of information in cyberspace.
Keywords: crime prevention; information technologies; interaction; international experience; national security; national legislation; network sovereignty; private interests; state system; cybersecurity